Inappropriate Antidiuretic Hormone Secretion and Cerebral Salt-Wasting Syndromes in Neurological Patients - Cui, Haiying; He, Guangyu; Yang, Shuo; Lv, You; Jiang, Zongmiao; Gang, Xiaokun; Wang, Guixia (Frontiers in Neuroscience, 2019)
The differential diagnosis of syndrome of inappropriate anti-diuretic hormone secretion (SIADH) and cerebral salt-wasting syndrome (CSWS) in patients with neurological disorders has been a perplexing clinical controversy. The purpose of this review is to summarize the characteristics and risk factors of patients with different types of neurological disorders complicated by hyponatremia (HN) and review various methods to distinguish SIADH from CSWS. Common neurological disorders with high rates of HN include subarachnoid hemorrhage, traumatic brain injuries, stroke, cerebral tumors, central nervous system (CNS) infections and Guillain-Barre syndrome, which have their own characteristics. Extracellular volume status of patients is a key point to differentiate SIADH and CSWS, and a comprehensive assessment of relevant extracellular volume indicators may be useful in differentiating those two syndromes. Besides, instead of monitoring the urinary sodium excretion, more attention should be paid to the total mass balance, including Na+, K+, Cl- and extracellular fluid. Furthermore, the dynamic detection of fractional excretions (FE) of urate before and after correction of HN and a short-term infusion of isotonic saline solution may be useful in identifying the etiology of hyponatremia. As for brain natriuretic peptide (BNP) or N-terminal prohormone of BNP (NT-proBNP), more prospective studies and strong evidence are needed to determine whether there is a pertinent and clear difference between SIADH and CSWS.